A Study of the Usefulness of Physical Models and Digital Models for Teaching Science to Prospective Primary School Teachers - F. Javier Robles-Moral; Manuel Fernández-Díaz; Gabriel Enrique Ayuso-Fernández (MDPI AG, 2023)
This study focuses on the impact of the use of teaching resources on future teachers in different formats, physical and digital. We worked with a single task dealing with nutrition in humans with two groups of students, but one group worked with a version of the task that used physical resources, and the other group used digital resources as tools. Analyzing the work carried out and the answers given by the future teachers, it has been possible to observe the advantage of using digital resources over physical ones, although it did not generate significant differences between the two groups of participating students. This study shows how convenient it is to increase the use of digital models because of their lower cost, greater availability and ease of use. In short, they argue that the teaching of scientific knowledge should be complemented by the use of resources and models that facilitate learning, regardless of the format of the resource used.